COVID-19, Rising Gold Prices and Illegal Mining Threaten Indigenous Lands in the Amazon (2020)
The Amazon contains world-class deposits of gold, copper, tin, nickel, iron ore and other industrial minerals. For decades, Amazonian governments have promoted and supported mining.